2013
DOI: 10.4236/ojst.2013.38076
|View full text |Cite
|
Sign up to set email alerts
|

The relationship among periodontal condition, serum lipid, and electrocardiographic abnormalities in the elderly: A prospective cohort study

Abstract: Periodontal disease is recognized as a risk factor for cardiovascular disease (CVD). Some studies have suggested that serum lipids might play a role in the association between periodontal disease and CVD. However, this hypothesis remains unproven. Present study evaluated the association between periodontal disease and CVD-related parameters including electrocardiographic (ECG) parameters and serum lipid levels in the elderly. This study was a prospective cohort study. A total of 107 subjects (57 males and 50 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In the elderly population, it is important to reduce the risk of systemic disease by controlling risk factors at an early stage. A number of researchers have suggested that periodontal disease may be a risk factor for systemic diseases such as cardiovascular disease, rheumatoid arthritis and metabolic syndrome (Ahmad et al., ; Furuta et al., ; Hanindriyo, Yoshihara, Hirotomi, & Miyazaki, ; Iwasaki et al., ; Pussinen et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the elderly population, it is important to reduce the risk of systemic disease by controlling risk factors at an early stage. A number of researchers have suggested that periodontal disease may be a risk factor for systemic diseases such as cardiovascular disease, rheumatoid arthritis and metabolic syndrome (Ahmad et al., ; Furuta et al., ; Hanindriyo, Yoshihara, Hirotomi, & Miyazaki, ; Iwasaki et al., ; Pussinen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…and metabolic syndrome (Ahmad et al, 2015;Furuta et al, 2016;Hanindriyo, Yoshihara, Hirotomi, & Miyazaki, 2013;Iwasaki et al, 2016;Pussinen et al, 2003).…”
mentioning
confidence: 99%
“…22 Associations between periodontal diseases and serum lipid levels was found in several studies. 23,24 On the hand, other studies found no relationship. 25,26 Review from Griffiths and Barbour suggests that periodontal diseases shifts the lipoprotein profile to be more proatherogenic.…”
Section: Introductionmentioning
confidence: 50%
“…Healthy oral conditions are necessary to maintain good nutritional status, which is one of the most influential factors of general health status . Moreover, impaired oral health is a significant risk factor for systemic disease among the elderly people . Therefore, reducing the risk of systemic disease by controlling risk factors at an early stage is important.…”
Section: Introductionmentioning
confidence: 99%
“…5 Moreover, impaired oral health is a significant risk factor for systemic disease among the elderly people. 8,9 Therefore, reducing the risk of systemic disease by controlling risk factors at an early stage is important.…”
mentioning
confidence: 99%